Governing (through) religion: reflections on religion as governmentality - Nasir, Muhammad Ali (Philosophy & social criticism, 2016)
This inquiry examines the question how the category of ‘religion’ generates a complex form of power oriented to the government of subjects. It does this through...
First published June 15, 2015
Gesehen am 12.08.2020